ANALYSIS OF GT 2.1 TRANSFORMER OIL TESTING USING THE DISSOLVED GAS ANALYSIS (DGA) METHOD AT PT PLN NUSANTARA POWER - Amsal Aritonang; Soni Prayogi (G-Tech: Jurnal Teknologi Terapan, 2025)
This study analyzes transformer oil from the GT 2.1 transformer at PT PLN Nusantara Power using the Dissolved Gas Analysis (DGA) method. Transformers are crucial for power systems, and their performance relies on the condition of their oil, which acts as both an insulator and a coolant. The DGA method detects gases like hydrogen, methane, ethylene, ethane, and acetylene in the oil, which indicate electrical or thermal faults. Oil samples were analyzed using diagnostic techniques such as the Rogers ratio, Duval triangle, and IEC standards to assess potential faults. The results revealed faults like thermal overheating and electrical discharges, offering valuable insights into the transformer’s health. The study highlights the importance of routine oil testing and DGA for predictive maintenance, enabling early fault detection. This proactive approach helps prevent failures, reduces outages, and extends transformer lifespan, ultimately enhancing the reliability and efficiency of power delivery at PT PLN Nusantara Power. The findings support the integration of advanced diagnostic methods in maintaining critical electrical infrastructure.